Development and evolution of mathematical and econometric models for the analysis of macroeconomic processes (including historical perspective) and their forecasting - A. P. Anufrieva (Вестник университета, 2024)
Practical usefulness of factor-vector autoregression has been considered, which makes it possible to study macroeconomic processes impact on the monetary policy state, to conduct full-scale monitoring and to identify economic growth impact on monetary policy. Publications devoted to the issues of unstable economic development and mathematical models describing the process of economic dynamics under conditions of high inflation and unstable development have been analyzed. The basic scenario in economy has been given. Monetary policy impact on macroeconomic variables using vector autoregressive (VAR) models has been studied. The FAVAR model with international reserves as the monetary policy variable and MIACR where the responses of one-year government bond rate and consumer index were positive have been estimated as the main instruments. The impulse responses shown indicate that the Russian authorities had a lack of monetary policy independence due to the country’s high dependence on the oil and natural gas sectors, which does not reveal evidence of monetary policy impact on lower consumer prices.